IMPLEMENTATION OF KLEDO APPLICATION – BASED FINANCIAL RECORDING AND INCOME TAX CALCULATION: (Case Study of Express Advertising in Pasuruan Regency) - Wahyudi, Imam; Martantina, Levi (Politeknik Negeri Ambon, 2026)
Introduction: This study aims to analyze the implementation of the Kledo application in financial recording and its impact on tax compliance among MSMEs. A case study was conducted at Express Advertising, a printing business located in Pasuruan Regency.Methods: This study used a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation.Result: The findings indicate that, prior to using Kledo, manual bookkeeping led to poorly organized financial statements. Since adopting the Kledo application, the recording process has become more systematic and compliant with SAK EMKM. The resulting financial reports are neater, more complete, and facilitate easier calculation of tax obligations. Express Advertising’s revenue from January to May 2025 amounts to IDR 561.487.000, subject to a Final Income Tax (PPh Final) of IDR 307.435. Furthermore, a simulation using the progressive tax rate showed a calculated tax liability of IDR 23.380.050. These results confirm that the use of digital accounting applications can enhance tax compliance and improve MSMEs’ preparedness in fulfilling bookkeeping requirements. The study concludes that accounting digitalization represents a strategic step for MSMEs to achieve greater compliance with tax regulations. Keywords: Financial Recording, Final Income Tax, Kledo Application, MSMEs, Tax Compliance